PEMANFAATAN DAUN SELADA SEBAGAI ALTERNATIF BAHAN PENGAWET ALAMI PADA DAGING AYAM BROILER: Utilization Of Lecttuca Leaves As An Alternative Natural Preservative For Broiler Chicken Meat - Imelinda Konga Naha; Yessy Tamu Ina (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2026)
This research was conducted to the evaluate effectiveness of fermented lecttuca leaf solution (lactuca sativa l) as a natural preservative to maintain the quality of broiler chicken meat during the storage process. The study was conducted at the Integrated Laboratory of Wira Wacana Christian University, Sumba. The manufacturing process was carried out by making a lettuce fermentation solution. The materials used were 100 g of broiler chicken meat and lettuce fermentation solution. This study used a Completely Randomized Design (CRD) with 4 treatments and 5 replications, namely: P1 (6%), P2 (9%) P3 (12%) P4 (15%) so that there were 20 sample units. The variables observed were pH, moisture content, organoleptic properties(color, taste, texture, and preference) and total protein. Data were analyzed using the ANOVA test at the 5% level and continued with the Duncan Multiple Range Test if there were significant differences. Organoleptic data were analyzed using the Kruskal-Wallis test and continued with the Mann-Whitney test. The results of the study showed that the lettuce leaf fermentation solution treatment significantly affected (P <0.05) the color, texture, and preference level. The 9% concentration treatment showed the lowest water content, so it was considered the most effective in maintaining meat quality. Based on the results of the study, the lettuce leaf fermentation solution has the potential as an alternative natural preservative in chicken meat.